2020
DOI: 10.21203/rs.3.rs-36506/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indiscriminate use of agro-veterinary pesticides in plague endemic foci in Tanzania: potential risk for development of insecticide resistance in flea vectors

Abstract: Background: Agro-veterinary pesticides are increasingly associated with the development of resistance in arthropod disease vectors. However, no has been conducted so far to assess such risk in flea vectors despite the indiscriminate use of pesticides in plague endemic foci in Tanzania.Methods: We identified risk factors associated with the use of agro-veterinary pesticides, which could enhance development of resistance in flea vectors in two plague endemic districts, using structured questionnaire and direct o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Some studies have also shown an association between the development of resistance in arthropod vectors and the application of agricultural pesticides. 51 In this study, resistance or tolerance of X. cheopis to permethrin and deltamethrin was detected as observed previously. 15,16 The use of pyrethroid-based insecticide formulations to control an and cockroach populations is a common practice throughout Madagascar, which also constitutes a credible hypothesis to explain the resistance profiles detected here.…”
Section: Discussionsupporting
confidence: 75%
“…Some studies have also shown an association between the development of resistance in arthropod vectors and the application of agricultural pesticides. 51 In this study, resistance or tolerance of X. cheopis to permethrin and deltamethrin was detected as observed previously. 15,16 The use of pyrethroid-based insecticide formulations to control an and cockroach populations is a common practice throughout Madagascar, which also constitutes a credible hypothesis to explain the resistance profiles detected here.…”
Section: Discussionsupporting
confidence: 75%
“…The mode of application of insecticides is very important for optimizing their functions especially as less than 1% of these applied insecticides get to their target organisms [16,17]. The over-reliance on chemical pesticides in combating pests throughout the world cannot be emphasized, yet it remains the most efficient, cheap and most accessible control mechanism in controlling pests [18]. Danquah et al [19] reports cases of organochlorine insecticides residues in Cameroon, Ghana and India within vegetable cultivation, water resources and soil sediments which results largely due to application malpractices.…”
Section: Application Methodsmentioning
confidence: 99%
“…In a studies conducted in Buea by Christos et al [21] about 76.4% tomatoes farmer use inappropriate or no PPEs during the application of insecticides, while Asongwe et al [23] shows that 95% of farmers in Bamenda Municipality do not protect themselves during pesticide applications. Rugalema and Mnyone [18] reported scenarios of insecticides sprinkling at homes with the hands.…”
Section: Application Without Personal Protective Equipment (Ppe)mentioning
confidence: 99%
“…En revanche, des traitements biocides visant des arthropodes ravageurs de cultures peuvent (au moins potentiellement) induire des résistances aux insecticides de synthèse chez ces puces (Rugalema et Mnyone, 2020) et aux acaricides chez les tiques Rhipicephalus/Boophilus vectrices d'anaplasmoses (Gondard et al, 2017 ;Kumar et al, 2020). Ces insecticides de synthèse ou acaricides favorisent ainsi indirectement les infections bactériennes, comme pour les moustiques vecteurs de zoonoses virales (Ratnadass et Deguine, 2021).…”
Section: Insecticides De Synthèseunclassified